(untitled) (Italian Review of Legal History, 2022)
The essay collects the reflections shared by the Author during the conference Dialogo transdisciplinare e identità del giurista organized by the Law Faculty of the University of Milan in September 2022. The dialogue with legal positivists who share with the law historians the task of training the jurists of future led to a reflection that retraced the research carried out in recent years, or currently in progress, by collaborating with colleagues from various legal and historical disciplines, on notaries, on criminal law, on administrative jurisdiction, on the repression carried out by the Special Tribunal for the Defense of the State in Libya during the Fascist period.